THE INFLUENCE OF ATTITUDE, SUBJECTIVE NORM, AND PERCEIVED BEHAVIORAL CONTROL ON ADOLESCENT MENTAL HEALTH HELP-SEEKING INTENTIONS - Ayu Anggreny Layang Donga; Annisa Nurrachmawati; Ike Anggraeni Gunawan; Nur Rohmah; Diah Rahayu; Muhammad Arifin (Jurnal Kesehatan Kusuma Husada, 2026)
Background: This study aimed to analyze the influence of attitude, subjective norm, and perceived behavioral control (PBC) on adolescents' mental health help-seeking intentions among high school students in North Sangatta. Methods: This study uses an observational, cross-sectional design. A sample of 551 respondents was collected via a structured questionnaire distributed via Google Forms to homeroom teachers and analyzed using multiple linear regression. Results: 43.9% of students with neutral attitude scores had high intentions to seek mental health help; 57.2% of students with high subjective norm scores had high intentions; and 43.9% of students with neutral perceived behavioral control (PBC) scores had high intentions. Parents were the source of health support for the majority of students, and the least accessed sources were online consultation services and through a boyfriend/girlfriend. The results of multiple linear regression tests showed that attitude (p-value: 0.015), subjective norm (p-value: 0.005), and PBC (p-value: 0.001) influenced the outcome, with a correlation coefficient of 7.4%. This means that the variables of attitude, subjective norm, and perceived behavioral control can explain 7.4% of the variation in mental health help-seeking. Conclusion: The findings reveal that PBC is the most influential variable in mental health help-seeking intention. Increasing mental health literacy for parents and teachers, community support, stigma reduction, and parent participation are necessary to enhance the values of attitude, subjective norm, and PBC among high school students in North Sangatta.